Posthuman feminism and global constitutionalism: Environmental reflections - Jones, Emily (Global constitutionalism, 2023)
There is a need for the field of global constitutionalism to consider a wider array of voices, such as women’s voices and perspectives from the Global South. Here, I argue that global constitutionalism must pay attention not only to a wider array of human perspectives, but also to non-human perspectives and to different understandings of what the law is and can be. Evaluating how international law categorizes the environment and non-human animals as things or objects to be exploited for human needs, I argue that posthuman feminism provides an alternative epistemic frame for rethinking both global constitutionalism and international law.